2014
DOI: 10.1111/vde.12105
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous involvement in canine leishmaniosis due to Leishmania infantum (syn. L.chagasi)

Abstract: Canine leishmaniosis due to L. infantum is characterized by diverse cutaneous manifestations that may reflect different host-parasite relationships. Furthermore, different types of skin lesions may occur, in various combinations, in the same dog. The definitive diagnosis of these lesions is based on clinical and laboratory examinations and on the response to antileishmanial treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
68
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(77 citation statements)
references
References 89 publications
(317 reference statements)
2
68
0
7
Order By: Relevance
“…The prevalence of microscopic lesions and detection of amastigotes either by routine histology or by IHC in our study was at the lower limit of the ranges reported in previous studies. Microscopic lesions have been noticed in 50–100% of the skin samples obtained from the normal-looking skin of dogs with CanL [5, 1214]. Moreover, amastigotes were seen in up to 100% of the cases, depending on the sensitivity of the method employed [5].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The prevalence of microscopic lesions and detection of amastigotes either by routine histology or by IHC in our study was at the lower limit of the ranges reported in previous studies. Microscopic lesions have been noticed in 50–100% of the skin samples obtained from the normal-looking skin of dogs with CanL [5, 1214]. Moreover, amastigotes were seen in up to 100% of the cases, depending on the sensitivity of the method employed [5].…”
Section: Discussionmentioning
confidence: 99%
“…Cutaneous lesions are the most common clinical signs in CanL [5] and they are very pleomorphic from a clinical and histopathological point of view as well [6]. The most common dermatological signs observed in dogs with leishmaniosis include exfoliative dermatitis, ulcerative dermatitis and onychogryphosis [5].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations